Functional swallowing outcomes following treatment for oropharyngeal carcinoma: a systematic review of the evidence comparing trans‐oral surgery versus non‐surgical management. (8th February 2016) - Dawe, N.; Patterson, J.; O'Hara, J.
Abstract : Background: Trans‐oral surgical and non‐surgical management options for oropharyngeal squamous cell carcinoma (OPSCC) appear to offer similar survival outcomes. Functional outcomes, in particular swallowing, have become of increasing interest in the debate regarding treatment options. Contemporary reviews on function following treatment frequently include surrogate markers and limit the value of comparative analysis. Objectives of review: A systematic review was performed to establish whether direct comparisons of swallowing outcomes could be made between trans‐oral surgical approaches (trans‐oral laser microsurgery (TLM)/trans‐oral robotic surgery (TORS)) and (chemo)radiotherapy ((C)RT). Type of review: Systematic review. Search strategy: MEDLINE, Embase and Cochrane databases were interrogated using the following MeSH terms: antineoplastic protocols, chemotherapy, radiotherapy, deglutition disorders, swallowing, lasers, and trans‐oral surgery. Evaluation method: Two authors performed independent systematic reviews and consensus was sought if opinions differed. The WHO ICF classification was applied to generate analysis based around body functions and structure, activity limitations and participation restriction. Results: Thirty‐seven citations were included in the analysis. Twenty‐six papers reported the outcomes for OPSCC treatment following primary (C)RT in 1377 patients, and 15 papers following contemporary trans‐oral approaches in 768 patients. Meta‐analysis was not feasible due to varying methodology and heterogeneity of outcome measures. Instrumental swallowing assessments were presented in 13/26 (C)RT versus 2/15 TLM/TORS papers. However, reporting methods of these studies were not standardised. This variety of outcome measures and the wide‐ranging intentions of authors applying the measures in individual studies limit any practical direct comparisons of the effects of treatment on swallowing outcomes between interventions. Conclusions: From the current evidence, no direct comparisons could be made of swallowing outcomes between the surgical and non‐surgical modalities. Swallowing is a multidimensional construct, and the range of assessments utilised by authors reflects the variety of available reporting methods. The MD Anderson Dysphagia Inventory is a subjective measure that allows limited comparison between the currently available heterogeneous data, and is explored in detail. The findings highlight that further research may identify the most appropriate tools for measuring swallowing in patients with OPSCC. Consensus should allow their standardised integration into future studies and randomised control trials.